Calretinin immunohistochemistry: A new cost-effective and easy method for diagnosis of Hirschsprung's disease - Lavanya Kannaiyan; Sujani Madabhushi; Ramani Malleboyina; Narendra Kumar Are; K Ramesh Reddy; Bhuvaneshwar Rao (Wolters Kluwer Medknow Publications, 2013)
Aim: To evaluate the efficacy of calretinin immunostaining in diagnosing Hirschsprung's disease (HD). Materials and Methods: Sixty cases were studied over a period of 1 year (July 2010-June 2011). There were 36 full-thickness biopsies and 24 resected specimens. Calretinin processing was done on the paraffin-embedded blocks after routine histopathological examination. Results: Of the 36 biopsy specimens, in 19 cases HD was diagnosed by hematoxylin and eosin (H and E) staining earlier. In 2 patients, ganglion cells were seen and HD was ruled out. In 15 cases, there was a diagnostic dilemma and calretinin was used. Ganglion cells were found in 3 specimens and nerve fibers in 5. In all 24 resected specimens, calretinin correlated with the findings on H and E staining. Conclusions: Calretinin was extremely useful in solving the suspicious and indeterminate cases of HD. It can serve as a valuable cost-effective diagnostic aid in the centers where acetylcholinesterase enzyme histochemistry is not available.